Pengalaman, Usability, dan Antarmuka Grafis: Sebuah Penelusuran Teoritis - Ruly Darmawan (ITB Journal Publisher, LPPM ITB, 2013)
Experience is a significant matter for human beings. Man obtains as well as constructs the meaning of life through his very own experience. By investigating human experience, one can become fully aware of humanity, the world, and the mutual relationship between both entities. On the other hand, experience in relation to existence can also be investigated in a wider context. In the context of usability, investigation of experience can make a significant contribution, for example, when determining the effectiveness and efficiency of a system and/or a product of technology. This paper discusses human experience and then correlates it to the concept of usability. It includes observation of several graphical user interfaces that serve as a medium between people and a product or a system. The expected result is an understanding of experience that will complement the existing concept of usability.